Efficacy and Safety of Adjunctive Aripiprazole, Metformin, and Paeoniae–Glycyrrhiza Decoction for Antipsychotic-Induced Hyperprolactinemia: A Network Meta-Analysis of Randomized Controlled Trials - Zhang, Ling; Qi, Han; Xie, Yun-Yi; Zheng, Wei; Liu, Xiao-Hui; Cai, Dong-Bin; Ng, Chee H.; Ungvari, Gabor S.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Aripiprazole, metformin and Paeoniae-Glycyrrhiza decoction (PGD) have been widely used as adjunctive treatments to reduce antipsychotic (AP)-induced hyperprolactinemia in patients with schizophrenia. However, the comparative efficacy and safety of these medications have not been previously studied. A network meta-analysis (NMA) of randomized controlled trials (RCTs) was conducted to compare the efficacy and safety between aripiprazole, metformin and PGD as adjunctive medications in reducing AP-induced hyperprolactinemia in schizophrenia. Both international (PubMed, PsycINFO, EMBASE, and Cochrane Library databases) and Chinese (WanFang, Chinese Biomedical and Chinese National Knowledge infrastructure) databases were searched from their inception until January 3th, 2019. Data were analyzed using the Bayesian Markov Chain Monte Carlo simulations with the WinBUGS software. A total of 62 RCTs with 5,550 participants were included in the meta-analysis. Of the 9 groups of treatments included, adjunctive aripiprazole (<5mg/d) was associated with the most significant reduction in prolactin levels compared to the other treatment groups (posterior mean difference = -65.52, 95% confidence interval (CI) = -104.91, -24.08). Moreover, adjunctive PGD (>1:1) was associated with the lowest rate of all-cause discontinuation (posterior odds ratio=0.45, 95%CI=0.10, 3.13) and adjunctive aripiprazole (>10mg/d) was associated with fewer total adverse drug events (posterior odds ratio=0.93, 95%CI=0.65, 1.77). In addition, when risperidone, amisulpride and olanzapine were the primary AP medications, adjunctive Paeoniae: Glycyrrhiza=1:1, aripiprazole<5mg/d, and aripiprazole>10mg/d were the most effective treatments in reducing prolactin levels. Adjunctive aripiprazole, metformin and PGD showed beneficial effects in reducing AP-induced hyperprolactinemia in schizophrenia, with aripiprazole (<5mg/d) being the most effective one.